Data Analytics of Hand, Foot & Mouth Disease (HFMD) using Geographic Information System (GIS)in Kuching Division, Sarawak - Busiai, Seman (Universiti Malaysia Sarawak (UNIMAS), 2021)
Hand, Foot and Mouth Disease (HFMD) is a common disease infecting young children and infants. Although it is a common disease, it can cause death if it is not treated at the early stage. Several studies have been conducted in relation to HFMD in Malaysia but the outcome of existing studies was too general to be used as a reference for mitigation planning. The highrisk area of HFMD at the residential area is yet to be revealed. As such, this study aims to identify the high-risk area of HFMD at the specified residential area in Kuching division. Kuching division has been chosen as a study area since it has recorded the highest number of HFMD within five years period (2014 to 2018) which was 7630 cases. In order to identify a high-risk area of HFMD, Geographic Information System (GIS) was used. To answer the research questions, several theories on disease transmission such as the epidemiological triangle, social determinants of health and Tobler’s first law of geography have been applied. The findings show that the high-risk areas are concentrated in the central area of Kuching city, namely Kampung Semariang Pinggir, Kampung Sungai Luar, Taman Heng Hua, Kampung Tabuan Jaya, Kampung Gita, Kampung Tupong Batu, Kampung Pinang Jawa, Kampung Masjid, Kampung Stapok and Taman Desa Matang. The results of this study are very significant as it contributes to the knowledge of the high-risk area of HFMD and also spatial spreading pattern of this disease in Kuching division from 2014 to 2018.